7+3(y-8)=23

Simple and best practice solution for 7+3(y-8)=23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+3(y-8)=23 equation:



7+3(y-8)=23
We move all terms to the left:
7+3(y-8)-(23)=0
We add all the numbers together, and all the variables
3(y-8)-16=0
We multiply parentheses
3y-24-16=0
We add all the numbers together, and all the variables
3y-40=0
We move all terms containing y to the left, all other terms to the right
3y=40
y=40/3
y=13+1/3

See similar equations:

| -½(x–6)=4 | | 900=j+309 | | 11x-4(3x-8)=37 | | 2(13x+18)=-23(x-4) | | –10t−4=2−9t | | 4(x-)=4x-5 | | 48*56=3*7*2c | | 5(10x+12)=-40(x-3) | | -5z+5=9 | | 6^(8x)=1.2^(11x+9) | | H=43+m | | 20(-12x+10)=38(x-2) | | 6/9=u/12u= | | 9+2(y-8)=24 | | 6^8x=1.2^11x+9 | | x+0.07x=22.90 | | (2x)°+(3x)°=90° | | 6/9=u/12= | | 54=12w-6w | | 20(-9x+12)=-8(x-4) | | -4-5=3g | | 0.65=x4 | | 12-6n=-36 | | 33=3(y+4)-6y | | 33=3y+12-6y | | 20(-11+8)=22(x-5) | | 4.5(3x+)-2x=7x-3(-2x+11) | | 20(-15x+24)=17(x-3) | | 60/;m=5 | | 20(-13x+21)=17(x-3) | | 15x-+20-2x=7x+6x-33 | | n+1-4n=-1 |

Equations solver categories